Modelling the sovereign debt strategy: A practical primer - Nicolas Audet; Adam Epp; Jeffrey Gao; Joe Ning (Bank of Canada, 2025)
This paper provides a primer on the role of debt modelling in developing a sovereign debt issuance strategy, and how the policy objectives of a sovereign debt manager influence design decisions within their models. The insights provided here are supported by current and past uses of the Canadian Debt Strategy Model, which is a key component of Canada's process to set its annual Debt Management Strategy and Medium-Term Debt Strategy. We address specific challenges that issuers of public debt often face. Those challenges include defining an appropriate objective function, specifying a strategy adaptable to an uncertain economic environment, operating within computational limitations and integrating qualitative considerations about liquidity and the needs of the investor base with quantitative assessments of costs and risks.
Keywords: G11; G17; H63; H68; 330; Debt management; Econometric and statistical methods; Financial markets; Fiscal policy